Optimising conditions for growth and xanthophyll production in continuous culture of Tisochrysis lutea using photobioreactor arrays and central composite design experiments. Issue 1 (2nd January 2017) - Beuzenberg, Veronica; Goodwin, Eric O.; Puddick, Jonathan; Romanazzi, Donato; Adams, Serean L.; Packer, Michael A.
ABSTRACT: The production of valuable metabolites from microalgae represents a potentially sustainable source of a range of products that can be difficult to synthesise directly. Microalgae respond to the dynamic and often subtly shifting growth environment in a complex way. The optimal conditions for growth can be quite different to those needed for optimal product generation, depending on the nature of the biosynthesis of that product. This is especially so for secondary metabolites. A combination of a multi-vessel photobioreactor array, where certain growth conditions can be monitored and controlled precisely together with an experimental design matrix has been used to determine the optimal combination of temperature, irradiance and pH for a group of xanthophylls including fucoxanthin in the algae Tisochrysis lutea in continuous culture. Continuous culture as a mode is more suited for industrial production than batch mode in which the media constituents and algal population change dramatically over time. The central composite design experiment matrix has a range of set values for each parameter being investigated that bracket the optimal conditions. The three parameters investigated in this work (temperature, irradiance and pH) are major factors influencing algal growth. The method can be applied to other parameters that might affect growth or might affect production of a metabolite of interest, such as a nutrient level. The combined approach has been used previously to indicate optimal growth conditions for biomass generation and this work is one of the first to apply it to the generation of an algal product of interest.